The Relevance of Islamic Jurisprudence (Fiqh) in Tackling Modern Issues - Ahsani Takwim; Fatimah Farah Yousif Farah; Dian Elfiani Risma; Titi Mildawati (Journal of Islamic Studies and Education, 2025)
This research explores the ongoing significance of Islamic law (fiqh) in tackling modern ethical challenges, including those arising from digital advancements, biotechnology, environmental changes, and shifting socio-economic frameworks. The study examine how fiqh adjusts to matters like digital financial systems, AI in medical decision-making, and bioethical challenges by integrating maqāṣid al-sharī‘ah and modern ijtihad. Utilizing a Systematic Literature Review (SLR), the research integrates fiqh with modern academic work to assess changes in methodology within Islamic law. The review highlights a notable transition from solely textual reasoning to a Maqāṣid al-Sharī‘ah that emphasizes public interest, justice, and contextual significance. Research indicates that collaborative and interdisciplinary approaches to ijtihad have become crucial for tackling complex modern ethical challenges, especially in areas that demand scientific and technological knowledge. Fiqh institutions are increasingly utilizing collective reasoning to guarantee trustworthy, evidence-based legal results. The research also underscores the increasing significance of fiqh in the ethics of the digital economy, bioethical oversight, and environmental management, where fiqh align with international standards. Despite this advancement, a significant research gap continues to exist in the practical use of Maqāṣid al-Sharī‘ah in policy, technology regulation, and actual legal decisions. In summary, the research finds that fiqh remains significantly relevant today when examined through vibrant, maqāṣid-oriented, and interdisciplinary approaches. Enhancing empirical and practical research is essential to guarantee that Islamic law remains a responsive, ethical, and solution-driven framework for addressing modern ethical challenges.